2019
DOI: 10.1080/17452759.2019.1677345
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure modelling for metallic additive manufacturing: a review

Abstract: The microstructure of metal built using AM is highly dependent on the process parameters. However, experimentation on different process parameters for different materials is costly and time consuming. To overcome these challenges, numerical simulations provide insights that allow prediction of microstructure formed under different process parameters. Microstructure modelling requires coupling of macro-scale thermal model or experimentally measured temperature profiles with either a meso-scale or micro-scale mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(75 citation statements)
references
References 138 publications
0
72
0
3
Order By: Relevance
“…Equiaxed cells (magnified in Figure 3 d) are found relatively far from the melt pool boundaries, while elongated cells (magnified in Figure 3 e) are distributed close to the melt pool boundaries and appear approximately perpendicular to the boundaries, which are formed in the beginning of solidification due to epitaxial growth. The formation of these two types of cells is ascribed to the different temperature gradient and solidification velocity at the solid–liquid interface in different locations of the melt pool, especially at the edge or the bottom [ 30 ]. Nano-inclusions are more likely to be embedded at cell walls ( Figure 3 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Equiaxed cells (magnified in Figure 3 d) are found relatively far from the melt pool boundaries, while elongated cells (magnified in Figure 3 e) are distributed close to the melt pool boundaries and appear approximately perpendicular to the boundaries, which are formed in the beginning of solidification due to epitaxial growth. The formation of these two types of cells is ascribed to the different temperature gradient and solidification velocity at the solid–liquid interface in different locations of the melt pool, especially at the edge or the bottom [ 30 ]. Nano-inclusions are more likely to be embedded at cell walls ( Figure 3 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Although several existing part orientation methods, such as the methods of Zhang et al (2016), Brika et al (2017), Cheng and To (2019) and Raju et al (2019), have considered some of these factors, the estimation models in them are either not for the LPBF process or incomplete. From other existing literature, such as the articles of Bartolomeu et al (2016), Mukherjee, Zhang, and DebRoy (2017), Vastola, Pei, and Zhang (2018), Li et al (2019) and Tan, Sing, and Yeong (2020), some related estimation models can be found. However, build orientation is not a variable in these models.…”
Section: Factor Value Estimationmentioning
confidence: 99%
“…Skeletal reconstruction of bone defects for load-bearing application is still a major challenge in orthopedic surgery. Solid metals and alloys such as stainless steel and titanium (Ti) have been successfully employed as bone implants owing to their excellent mechanical and bio-logical properties [1]. However, stress-shielding and impermeability have limited their applications [2].…”
Section: Introductionmentioning
confidence: 99%